فرفرية هينوخ شونلاين دراسة وبائية وسريرية وعلاجية - زعبلاوي يوسف; ميهوب محمد; مصطفى لبانه (Latakia University Journal -Medical Sciences Series, 2019)
شملت دراستنا(25) مريضاً من المرضى المقبولين في قسم الأطفال في مشفى الأسد الجامعي باللاذقية بتشخيص مبدئي حالة فرفرية هينوخ شونلاين خلال مدة الدراسة(عام واحد من1/8/2005 لغاية 1/8/2006 ). توزع المرضى على الشكل الآتي: " 15" ذكور (%60) من الحالات، و"10"إناث ( %40)من الحالات. وجدت الفرفريات في كل الحالات (%100) مع توضع أشيع على الطرفيين السفليين (%100)، الألم المفصلي كان أشيع الأعراض التي ترافقت مع الفرفرية 23 حالة (92%) الإصابة الهضمية مع الألم البطني وجد في "13"حالة (%52)، في"10"حالات (%40) وجدت البيلة الدموية أو البيلة البروتينية، مما يشير للإصابة الكلوية. بمتابعة20 مريضاً لفترة تراوحت من شهرين حتى 6 أشهر "15" حالة (%75) كانت طبيعية، حدثت معاودة للفرفريات في "3" حالات (%15)، معاودة الألم البطني في "2" حالة (%10)، الآلام المفصلية المعاودة في "2" حالة (%10)، تغيرات فحص البول "1" حالة (%5). Our study included 25 patients from those who were admitted to the Department of Pediatrics at AL Assad University Hospital in Lattakia diagnosed of Henoch-Schönlein purpura during one year from 1/8/2005 to 1/8/2006. The study included 15 males (60%) and 10 females (40%). Purpura was seen in all patients (100 %) with lower extremities being the commonest site of involvement (100%). Joint pain was the commonest symptom accompanying the purpura seen in 23 patients (92%), gastrointestinal tract involvement with findings of abdominal pain in 13 patients (52%, 40% (10 cases) and abnormal urinalysis with microscopic haematuria or proteinuria, indicating renal involvement. In the follow up of 20 patients for 2 - 6 months 15 cases (75%) were normal, recurrent purpura was seen in 3 cases (15%), recurrent abdominal pain seen in 2 cases (10%), recurrent joint pain seen in 2 cases (10%), urine abnormalities seen in 1 case (5%).